RP-UPLC method development and validation for the simultaneous estimation of montelukast and ebastine in bulk and pharmaceutical dosage form - Amaresha S; Rakesh K Jhat (International Journal of Pharmacy and Analytical Research, 2022)
A simple, accurate, precise and reliable RP-UPLC method was developed for the simultaneous estimation of the Montelukast and Ebastine in pharmaceutical dosage form. Mobile phase with 0.1% Ortho phosphoric acid: Acetonitrile in the ratio of 60:40 run through Waters C18 150 x 3 mm, 2m.column at a rate of 0.3ml/min. at temperature 30°C and optimized wavelength was set at 244nm. Retention time of Montelukast and Ebastine were found to be 1.298 min and 1.636 min. The method developed was validated in accordance with ICH guidelines with respect to the stability indicating capacity of the method including system suitability, accuracy, precision, linearity, range, limit of detection, limit of quantification and robustness. This method passed all the validation parameters; hence, it can be employed for routine quality control of Montelukast and Ebastine in pharmaceutical industries and drug testing laboratories.